ANALYZING THE TRANSITION FROM CASH TRANSACTIONS TO DIGITAL PAYMENT PLATFORMS: IMPLICATIONS AND CYBERSECURITY THREATS - Kaur, Navneet (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research examines the shift in banking transactions from traditional cash methods to digital payment platforms like Paytm. It explores socio-economic impacts, changes in consumer behavior, and addresses cybersecurity threats that come with the digital shift. Using secondary data from RBI Payment System Indicators, NPCI reports, and CERT-In cybersecurity incident reports, the study employs statistical analysis and machine learning techniques to identify and reduce cyber threats, providing insights into the benefits and risks of digital payments.